THE RESISTANCE OF WOOD PLASTIC COMPOSITE TO THE DRY-WOOD TERMITE Cryptotermes cynocephalus Light. AND THE SUBTERRANEAN TERMITE Coptotermes curvignathus Holmgren INFESTATION - Jasni Jasni; Nurwati Hadjib; Barly Barly; Yusuf Sudo Hadi; Y. Afidudin (Indonesian Journal of Forestry Research, 2004)
Wood  plastic  composites   (WPC) were made  by impregnating  monomer   and  vinyl acetate monomer  with addition  of  terbutyl peroxide  catalyst. This laboratory  scale experiment  aimed at looking into  the durability of  WPC polymerized  at varying mixture  ratios between  styrene and vinyl acetate monomers,  compared  to the natural   durability of  the corresponding   wood  treated with impralit CKB.  In this  regard,  wood  samples were dried until 10 % moisture  content,   and then  they were put in the tank under  20 mm Hg vacuum was being released.   Styrene  monomer with vinyl acetate  addition was flown to the tank, and the wood  samples were immersed  in the monomer   for  24 hours.   Furthermore,   the wood  samples  were taken  out,  and  wrapped  with aluminum  foil, and then were   put in the oven for 24 hours at 60° C. The  wraps were opened, and the samples were  conditioned.   The  samples were tested  to dry wood  termite  (Cryptotermes cynocephalus Light.),  and the Subterranean  termite (Coptotermes curvignathus Holmgren.).  Investigated factors were (i) wood species consisting of sengon, pine, and rubber wood, and (ii) ratio of styrene to vinyl acetate. i.e.  90/10;  80/20;  70/30;  and 60/40.   For comparison,  each wood samples  treated with  Impralit  CKB  3% and untreated   (unpolymerized)    wood  samples  (a control)  were  also prepared.  The  results showed  that polymer  loadings  in the  sengon, pine and rubber  wood were 118 %, 72 % and  44%  respectively. Increasing  of  vinyl acetate  to styrene  tended  to decrease polymer loading,  the addition  of  10% gave 96% polymer  loading,  20% gave 108%,  30% gave 71 %, and 30% gave 38 % respectively.  It appeared that treatment  of styrene with low vinyl acetate additions  (60:40) had resulted  in consecutively  95.67%  and 97.75 % mortality  of  the dry wood termite  and sub subterranean   termite. This implied  that the treatment  might increase the wood resistance  to the wood destroying insect.